Checkout or Scroll Down? Investigating TikTok’ Influencer Credibility Effects on Followers' Purchase Intentions - Prasetyo, Salsabil Dwi Kusuma; Sobari, Nurdin (Jurnal Manajemen Teori dan Terapan| Journal of Theoretical and Applied Management, 2024)
Objective: This study explores the influence of influencer credibility on consumer purchasing intentions on TikTok, focusing on the Indonesian market. It examines the mediating roles of trust and online engagement in the relationship between influencer credibility and purchasing intentions, providing insights into influencer marketing strategies. Design/Methods/Approach: A quantitative approach was employed, using questionnaires to collect data from 356 TikTok users who had made purchases on TikTok. Regression analysis tested the relationships between influencer credibility, trust, online engagement, and purchase intention. Findings: The study found that attractiveness positively and significantly impacts credibility, trust, and purchase intention. Credibility also positively influences trust. Furthermore, trust and online engagement are positively linked to purchase intention. While reliability and expertise positively influence credibility and online engagement, they do not significantly impact purchase intention. Originality/Value: This research applies the SOR (Stimulus-Organism-Response) model by examining the impact of influencer credibility factors—physical attractiveness, reliability/honesty, and expertise—on purchase intention, mediated by trust and online engagement. It provides empirical evidence and a theoretical framework for understanding consumer behavior in TikTok influencer marketing campaigns. Practical/Policy Implication: Our results provide a deeper understanding of how TikTok influencer's credibility can influence trust, online engagement, and consumer purchasing intentions in TikTok. The practical implications of this research can guide companies in improving their relationship marketing strategies, significantly increasing consumer purchasing intentions. In addition, the theoretical contribution of this research can improve understanding of the concept of influencer credibility and provide a summary of trust, online engagement, and purchase intention.